2012
DOI: 10.1123/ijsc.5.4.539
|View full text |Cite
|
Sign up to set email alerts
|

Identity in Twitter’s Hashtag Culture: A Sport-Media-Consumption Case Study

Abstract: This case study, using social-identity theory as a framework, examines how sport consumers and producers used different identifiers to engage in conversation during the final games of the 2012 College World Series of baseball. Five major hashtags were noted for each baseball team as primary identifiers; users fit in 3 main groups and subgroups. The analysis of tweets revealed 5 major themes around which the conversations primarily revolved. The study has implications for social-identity theory and team identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Previous studies have suggested interesting and important possible relationships between social media and team identification that could widen the adoption of social media in sports. In other word, social media consumption could increase the level of team identification (Gau, James, & Kim, 2009;Gray & Wert-Gray, 2012;Matsuoka, Chelladurai, & Harada, 2003;Smith, Smith, & Sanderson, 2012). Trail, Anderson, and Fink (2000) defined identification as "an orientation of the self in regard to other objects including a person or group that result in feelings or sentiments of close attachment" (p. 165-166).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have suggested interesting and important possible relationships between social media and team identification that could widen the adoption of social media in sports. In other word, social media consumption could increase the level of team identification (Gau, James, & Kim, 2009;Gray & Wert-Gray, 2012;Matsuoka, Chelladurai, & Harada, 2003;Smith, Smith, & Sanderson, 2012). Trail, Anderson, and Fink (2000) defined identification as "an orientation of the self in regard to other objects including a person or group that result in feelings or sentiments of close attachment" (p. 165-166).…”
Section: Introductionmentioning
confidence: 99%
“…Since social media increases team awareness (Shirky, 2011), it would be logical that social media consumption would develop team identification. Moreover, there are more evidences indicating the relationship between media consumption and team identification (Gau et al, 2009;Smith et al, 2012). Gau et al (2009) analyzed a total of 750 spectators from three baseball and three softball games.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of sociocultural topics, scholars have revealed that Twitter can be used as a vehicle to discuss issues related to flaws in the American justice system and freedom of speech . In that regard, scholars have argued that Twitter is in fact the new watercooler (Smith & Smith, 2012), allowing users to engage in digital conversations on a global scale.…”
mentioning
confidence: 99%